2000
DOI: 10.1164/ajrccm.161.2.9902040
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of Transbronchial Needle Aspiration in the Staging of Bronchogenic Carcinoma

Abstract: We conducted a prospective multi-institutional clinical study involving community hospitals and academic medical centers to more carefully define the value of computerized tomography (CT) of the chest with transbronchial needle aspiration (TBNA) in the staging of bronchogenic carcinoma (CA), and to assess the predictors of a positive aspirate. Of 360 individuals determined to have bronchogenic carcinoma, 50 of 81 (62%) with small cell carcinoma (SCC) and 135 of 279 (48%) with non-small cell carcinoma (NSCC) ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
140
3
16

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(169 citation statements)
references
References 25 publications
10
140
3
16
Order By: Relevance
“…This trend was also described by Harrow et al [20]. The paper describes a linear relationship between diagnostic yield from TBNA and lymph node size: up to 2.5 cm, the larger the lymph node the higher the diagnostic yield [20]. TBNA has an excellent safety profile with no case reports of mortality from the procedure.…”
Section: Transbronchial Needle Aspirationsupporting
confidence: 56%
See 1 more Smart Citation
“…This trend was also described by Harrow et al [20]. The paper describes a linear relationship between diagnostic yield from TBNA and lymph node size: up to 2.5 cm, the larger the lymph node the higher the diagnostic yield [20]. TBNA has an excellent safety profile with no case reports of mortality from the procedure.…”
Section: Transbronchial Needle Aspirationsupporting
confidence: 56%
“…A study by Patelli et al demonstrated a higher diagnostic yield for TBNA comparing right paratracheal nodes (sensitivity 84%) and subcarinal nodes (sensitivity 79%) with left paratracheal nodes (station 4L; 52%) [19]. This trend was also described by Harrow et al [20]. The paper describes a linear relationship between diagnostic yield from TBNA and lymph node size: up to 2.5 cm, the larger the lymph node the higher the diagnostic yield [20].…”
Section: Transbronchial Needle Aspirationmentioning
confidence: 73%
“…1 The same could be said about fine needle aspiration of enlarged mediastinal lymph nodes, albeit for different reasons. In this case, the frustration lies in the difficulty in reproducing the diagnostic yield of very experienced hospitals, 2 especially those, such as ours, that are fortunate enough to have a histopathologist present during the procedure.…”
Section: Introductionmentioning
confidence: 96%
“…When similar studies in the literature were reviewed, it was found that the sensitivity of TBNA was higher in left-sided compared to right-sided tumors, and in right paratracheal and subcranial lymph node aspirates compared to left paratracheal aspirates (9).…”
Section: Factors Affecting the Success Of Tbnamentioning
confidence: 97%